2023
DOI: 10.1002/adma.202306281
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Fusobacterium nucleatum‐Mimicking Nanomedicine to Selectively Eliminate Tumor‐Colonized Bacteria and Enhance Immunotherapy Against Colorectal Cancer

Linfu Chen,
Rui Zhao,
Jingjing Shen
et al.

Abstract: Clinical evidence has indicated that tumor‐colonizing bacteria would be closely related to the tumor development and therapeutic responses. Selectively eliminating bacteria within tumors may be an attractive approach to enhance cancer treatment without additional side effects. Herein, we found that owing to the high affinity between the membrane protein Fap‐2 on Fusobacterium nucleatum (F. nucleatum) and D‐galactose‐β (1‐3)‐N‐acetyl‐D‐galactosamine (Gal‐GalNAc) overexpressed on colorectal tumor cells, F. nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…And this nanomedicine selectively eliminates F. nucleatum while leaving other gut microbes unharmed, ultimately restoring ICIs treatment effectiveness in tumors colonized by F. nucleatum. 40 Simultaneously, probiotics also increase tumor sensitivity to ICI treatment. To manipulate the gut microbiome, the scientists employed Probio-M9, a strain of Lacticaseibacillus rhamnosus.…”
Section: Discussionmentioning
confidence: 99%
“…And this nanomedicine selectively eliminates F. nucleatum while leaving other gut microbes unharmed, ultimately restoring ICIs treatment effectiveness in tumors colonized by F. nucleatum. 40 Simultaneously, probiotics also increase tumor sensitivity to ICI treatment. To manipulate the gut microbiome, the scientists employed Probio-M9, a strain of Lacticaseibacillus rhamnosus.…”
Section: Discussionmentioning
confidence: 99%
“…MTI-FDU reshapes the TIME by eliminating bacteria and bacterial byproducts, demonstrating clinical benefits in treating tumors infiltrated with bacteria as this nanomedicine can effectively kill tumor-promoting bacteria while maintaining the patient’s microbiome balance. Additionally, Chen et al recently reported a Fusobacterium-targeted liposome designed for colorectal cancer treatment, which is able to targetedly deliver antibiotics to immunosuppressive bacteria . This approach aims to overcome immune therapy resistance caused by tumor-colonizing bacteria.…”
Section: Intratumoral Bacterial Clearancementioning
confidence: 99%
“…Additionally, Chen et al recently reported a Fusobacterium-targeted liposome designed for colorectal cancer treatment, which is able to targetedly deliver antibiotics to immunosuppressive bacteria. 67 This approach aims to overcome immune therapy resistance caused by tumorcolonizing bacteria.…”
Section: Intratumoral Bacterial Clearancementioning
confidence: 99%
“…Chen et al 72 designed a liposome-based nanomedicine that mimics F. nucleatum to reverse immunotherapy resistance for the infected CRC treatment (Fig. 7a and b).…”
Section: Nanomaterials For Bacteria-related Tumor Therapymentioning
confidence: 99%